2002
DOI: 10.1046/j.1462-5822.2002.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Brucella-induced macropinocytosis by lipid rafts mediates intracellular replication

Abstract: Summary Intracellular replication of Brucella requires the VirB complex, which is highly similar to conjugative DNA transfer systems. In this study, we show that Brucella internalizes into macrophages by swimming on the cell surface with generalized membrane ruffling for several minutes, after which the bacteria are enclosed by macropinosomes. Lipid raft‐associated molecules such as glycosylphosphatidylinositol (GPI)‐anchored proteins, GM1 gangliosides and cholesterol were selectively incorporated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
145
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(153 citation statements)
references
References 57 publications
(67 reference statements)
5
145
1
2
Order By: Relevance
“…Neither virulence factors that allow intracellular survival of Brucella species nor the specific factors that induce such virulence have been elucidated. B. abortus is internalized by macrophages by swimming on the cell surface with generalized membrane ruffling for several minutes, a process termed 'swimming internalization', after which the bacteria are enclosed by macropinosomes (Watarai et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither virulence factors that allow intracellular survival of Brucella species nor the specific factors that induce such virulence have been elucidated. B. abortus is internalized by macrophages by swimming on the cell surface with generalized membrane ruffling for several minutes, a process termed 'swimming internalization', after which the bacteria are enclosed by macropinosomes (Watarai et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…Neither virulence factors that allow intracellular survival of Brucella species nor the specific factors that induce such virulence have been elucidated. B. abortus is internalized by macrophages by swimming on the cell surface with generalized membrane ruffling for several minutes, a process termed 'swimming internalization', after which the bacteria are enclosed by macropinosomes (Watarai et al, 2002a).Recently we showed that Hsp60, a member of the GroEL family of chaperonins, of B. abortus is secreted on the bacterial surface through a type IV system and can interact with the cellular prion protein (PrP G ) on macrophages (Watarai et al, 2003 vacuoles rapidly fuse with early autophagosomes that acquire vacuolar H + -ATPase and lysosome-associated membrane proteins (LAMPs), mature into late autophagosomes, inhibit fusion with lysosomes and finally become replicating vacuoles, normally associated with the endoplasmic reticulum (Comerci et al, 2001; Pizarro-Cerda et al, 1998a, b). The genetic basis of B.abortus virulence is still poorly understood.…”
mentioning
confidence: 99%
“…Immature dendritic cells and macrophages both continuously take up their surrounding fluid by macropinocytosis to sample their environment and capture antigens for presentation (8). Unfortunately this process can provide a way for pathogens to gain entry into host cells and is thus exploited by a number of infectious agents such as viruses, bacteria, and even prions (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…This operon is composed of 13 open reading frames (ORFs) that share homology with other bacterial type IV secretion systems in the intracellular trafficking of pathogens. Deletion or polar and non-polar mutations of these ORFs were not able to replicate and survive within phagocytes [19,21], and internalization and uptake pathway in phagosome trafficking between wildtype and virB mutant showed different patterns [11]. Thus, the VirB proteins of B. abortus are thought to be constituents of the secretion apparatus.…”
mentioning
confidence: 99%